Tear Cathepsin S–A Candidate Biomarker for Sjögren's Syndrome - Hamm-Alvarez, Sarah F. (2014)
OBJECTIVE: The diagnosis of Sjögren's Syndrome (SS) in routine practice is largely a clinical one and requires a high index of suspicion by the treating physician. This great dependence upon clinical judgment frequently leads to delayed diagnosis or misdiagnosis. Tear protein profiles have been proposed as simple and reliable biomarkers for SS diagnosis. Given that cathepsin S activity is increased in the lacrimal glands and tears of NOD mice (a murine model of SS), we explored the clinical utility of using tear cathepsin S (CTSS) activity as a biomarker for SS. METHODS: A method to measure CTSS activity in tears eluted from Schirmer's strips was developed and validated. Schirmer's tests and CTSS activity measurements were performed on 278 female subjects, including patients with SS (n=73), rheumatoid arthritis (n=79), systemic lupus erythematosus (n=40), blepharitis (n=10), non-specific dry eye (n=31), or other autoimmune diseases (n=12), along with 33 healthy controls. RESULTS: Median tear CTSS activity in SS patients was 4.1-fold higher than in patients with non-SS autoimmune diseases, 2.1-fold higher than in patients with non-specific dry eye, and 41.1-fold higher than in healthy controls. Tear CTSS levels were equally elevated in primary and secondary SS independent of the Schirmer's strip values or of circulating anti-SSA or anti-SSB autoantibodies. CONCLUSION: Markedly high levels of tear CTSS activity are suggestive of SS. CTSS activity in tears can be measured in a simple, quick, economical, and non-invasive fashion and may serve as a novel biomarker and indicator of autoimmune dacryoadenitis during the workup for SS.